Implementasi Strategi Cooperative Learning Dalam Pembelajaran - Atikah Atikah; Fatya Ayuni; Irsal Hidayat; Gusmaneli Gusmaneli (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This article aims to describe (tell) about the implementation of cooperative learning strategies in learning. This research uses library research methodology and is qualitative because the data collected uses textual analysis contained in books and journals related to learning strategies. The results of this research are first, in this study it was found that the implementation of cooperative learning strategies had a positive impact on students' ability to understand learning. Second, students have the opportunity to speak and express opinions in providing ideas for learning.